An Overview of Structural Features of Antibacterial Glycoconjugate Vaccines That Influence Their Immunogenicity. Issue 18 (18th January 2017) - Khatun, Farjana; Stephenson, Rachel J.; Toth, Istvan
Abstract: Bacterial cell‐surface‐derived or mimicked carbohydrate moieties that act as protective antigens are used in the development of antibacterial glycoconjugate vaccines. The carbohydrate antigen must have a minimum length or size to maintain the conformational structure of the antigenic epitope(s). The presence or absence of O ‐acetate, phosphate, glycerol phosphate and pyruvate ketal plays a vital role in defining the immunogenicity of the carbohydrate antigen. The nature of the carrier protein, spacer and conjugation pattern used to develop the glycoconjugate vaccine also defines its overall spatial orientation which in turn affects its avidity and selectivity of interaction with the desired target(s). In addition, the ratio of carbohydrate to protein in glycoconjugate vaccines also makes an important contribution in determining the optimum immunological response. This Review article presents the importance of these variables in the development of antibacterial glycoconjugate vaccines and their effects on immune efficacy. Abstract : Design for life : The avidity and selectivity of glycoconjugate vaccines (see scheme) is dependent on key factors, such as the choice of carbohydrate antigen, immunogenic carrier molecule, conjugation strategy, ratio of carbohydrate to carrier protein, and the spacer used for the conjugation process. This Review article presents the importance of the variables governing the development of antibacterial glycoconjugate vaccines and their effects on immune efficacy.